Clinical & Microbiological profile of Fourniers Gangrene in a Tertiary Care Hospital in Bangladesh : A prospective observational study - Maitra, Tapash Kumar; Ekramullah, Mahmud; Shabnam, Nilufar; Roy, Sharmistha; Mondol, Samiran Kumar (Bangladesh Critical Care Journal, 2017)
Background: Fourniers gangrene is the necrotising fasciitis of the genitalia and perineum, with associated poly microbial infection. Evidence based data in the very recent years suggest that it is associated with significant and potential risk of organ failure or death. Aim: This study was designed to be conducted among the patients suffering from Fourniers gangrene with a view to assess the probable prevalence rate of potentially adverse clinical consequences during course of treatment, overall mortality and to observe the microbiological pattern in our surgical practice. Method & materials: This cross sectional study was conducted among the 69 patients of Fourniers gangrene in BIRDEM General Hospital, Dhaka, Bangladesh from Jan 10.2013 to Sept 01 .2016, using the purposive sampling method. Results: The results of this study reflects that majority (43.4%) of the study population were in 51 to 60 years age group( Mean age 43±1.7 years) in study population. By using the Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score, it was found that in most of the patients (approx 56.5%), a suspicious score ranging 06-08 was observed and only in 10.1% patients, a specific score of ?08 was observed. In 27.5% patients systemic complications like DIC, ARDS, MODS, MSOF and severe sepsis were observed in 1.4%, 4.3%, 10.1%, 4.3% and 5.7% cases respectively. Mortality rate was approximately 4.3%. Majority (84.1%) of the patients were associated with type 1 (Polymicrobial) bacterial infection, whereas in case of 15.9% patients, it was associated with type 2 (Monomicrobial) infection. Escherichia coli was the most frequently observed micro-organisms associated with approximately 39.1% of all cases. S. aureus, Staphylococcus pyogenes, Enterococci species, E.coli and Pseudomonas species were recorded to be associated with 17.4%, 27.5%, 21.7%, 39.1 and 10.1% cases respectively. Conclusion: This study suggests that Fourniers gangrene is associated with significant systemic complications. Poly microbial infections are most predominant and E coli infection was commonest organism involved. Bangladesh Crit Care J March 2017; 5(1): 28-32